Insulin signaling mediates sexual attractiveness in Drosophila. - Kuo, T.H.; Fedina, T.Y.; Hansen, I.; Dreisewerd, K.; Dierick, H.A.; Yew, J.Y.; Pletcher, S.D. (PLoS Genetics, 2012)
Sexually attractive characteristics are often thought to reflect an individual's condition or reproductive potential, but the underlying molecular mechanisms through which they do so are generally unknown. Insulin/insulin-like growth factor signaling (IIS) is known to modulate aging, reproduction, and stress resistance in several species and to contribute to variability of these traits in natural populations. Here we show that IIS determines sexual attractiveness in Drosophila through transcriptional regulation of genes involved in the production of cuticular hydrocarbons (CHC), many of which function as pheromones. Using traditional gas chromatography/mass spectrometry (GC/MS) together with newly introduced laser desorption/ionization orthogonal time-of-flight mass spectrometry (LDI-MS) we establish that CHC profiles are significantly affected by genetic manipulations that target IIS. Manipulations that reduce IIS also reduce attractiveness, while females with increased IIS are significantly more attractive than wild-type animals. IIS effects on attractiveness are mediated by changes in CHC profiles. Insulin signaling influences CHC through pathways that are likely independent of dFOXO and that may involve the nutrient-sensing Target of Rapamycin (TOR) pathway. These results suggest that the activity of conserved molecular regulators of longevity and reproductive output may manifest in different species as external characteristics that are perceived as honest indicators of fitness potential.